Targeted hearing screening in newborns - Mehar, Veerendra; Somani, Pavan; Singh, Kuldeep; Munjal, Vishal R. (International Journal of Contemporary Pediatrics, 2016)
Background: Hearing is important for learning to talk. With-out speech and hearing it is difficult for interpersonal relationships to develop and thrive The aim of this study was to screen high risk newborn for hearing loss by TEOAE and ABER technique and to find out the risk factor associated with hearing loss in newborn infants. Methods: A total of 103 high risk neonates were randomly selected from NICU of this hospital after clinical stabilization. Transiently evoked otoacoustic emissions were performed in all the neonates. Neonates who passed transiently evoked otoacoustic emissions test were subjected to Auditory Brainstem Evoked Response (ABER) test for confirming hearing loss. Results: Hearing assessment done in all 103 patients and a total of 8 neonates were found to have hearing abnormalities, out of these 8 new-borns 5 had conductive hearing loss and 3 had sensorineural hearing loss. Low Birth weight and ventilator support were observed significantly associated with occurrence of hearing loss. No significant association of hearing loss was observed with gestational age, sex, infection, and associated diseases. Conclusions: Low Birth weight and mechanical ventilator were significantly associated with hearing loss.